Impacts of temperature and water table manipulation on grassland phenology. Issue 4 (9th May 2014) - Cornelius, Christine; Heinichen, Jan; Drösler, Matthias; Menzel, Annette; Güsewell, Sabine
Abstract Question Re‐wetting drained peatlands is a common restoration method to reduce carbon loss, but little is known on its likely consequences on reproductive plant development, especially in a warming world. Thus, the aim of this study was to test whether the phenological development of plant species in a peatland ecosystem changed with higher temperatures, increased water table level or a combination of the two. Location Fen peatland site in Bavaria, Germany. Methods In 2010, manipulative experiments with two different treatments (control and warming) and in 2011 with four different treatments (control, warming, increased water table level, warming + increased water table level) were conducted. Temperature was raised 0.4–1.5 °C with open‐top chambers (OTCs) from August 2009 onwards, and water table level was elevated 12 cm using a pumping system, however the latter was not continuous for the whole growing season of 2011 due to technical difficulties. Phenological development of different grassland species was observed weekly using the BBCH code. Attention focused on reproductive phenology (from flower development to fruit senescence) and on key single phenological phases, such as flower development, flowering, ripening and fruit senescence, as well as the duration of key phases. Additionally, vegetation height was measured. Results Our study showed that higher temperatures advanced reproductive phenology and most key phases, except fruit senescence. Water table manipulations had no significant influence on phenology. The duration of key phases was generally not significantly influenced by treatments, whereas vegetation height differed between control and higher temperature plots. Conclusion In general, raising the water table to reduce carbon release from drained peatland sites will not dramatically affect phenological development of grassland species, whereas increased temperatures will affect reproductive phenology.